Tailored piezoelectric performance of self‐polarized PVDF‐ZnO composites by optimization of aspect ratio of ZnO nanorods. Issue 8 (17th July 2020) - Pratihar, Shewli; Medda, Samar Kumar; Sen, Shrabanee; Devi, P. Sujatha
Abstract: Aspect ratio of filler plays a crucial role to study the electrical properties of polymer based composite system. Here, we investigated the effect of filler aspect ratio on the electrical properties of zinc oxide (ZnO) incorporated poly(vinylidene fluoride) (PVDF) matrix. ZnO nanorods having different aspect ratio were synthesized by the hydrothermal technique with varying reaction time 4 to 20 hours at a fixed temperature and PVDF based nanocomposites of the respective ZnO nanorods with different wt% filler loading were fabricated. Interestingly polar‐phase fraction increased with the aspect ratio of ZnO nanorods. The nanocomposites with higher aspect ratio ZnO nanorods showed an increased energy density under same electric field and exhibited maximum open circuit AC output voltage (ie, 20 V) after the application of repeated human finger tapping. This result indicates that high aspect ratio ceramic filler provides an effective approach to enhance the dielectric, ferroelectric, energy storage, and energy harvesting performances of ceramic‐polymer nanocomposites. Abstract :